MODERN TRENDS IN THE DEVELOPMENT OF COMPETITIVE ACTIVITIES IN AIKIDO IN RUSSIA - Sobyanin, F.I.; Beketov, O.V.; Malakhov, V.A.; Filatov, M.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify trends in the development of aikido in Russia based on the analysis of the results of competitive activity. Methods and structure of the study. The work was carried out as part of the research activities of the National Aikido Council of Russia. Representatives of the Regional Public Organization "Belgorod Interstyle Aikido Federation" and teachers of "Belgorod State National Research University" took part in it. An analysis was made of the protocols of the Russian Aikido Championships and competitions for the Aikido Cup in 2020-2022. Results of the study and their discussion. All-Russian aikido competitions are held in the following competitive disciplines for both men and women: kihon-waza (doubles), jui-waza (doubles), jui-waza (group category). The hypothesis is considered that in recent years, more and more young athletes under the age of 21 have been winning competitions. As the study showed, the winners and prize-winners of aikido competitions among women are indeed becoming more and more young athletes, but the bulk of the participants in the competitions are women about 30 years old. Tendencies for rejuvenation of all participants of the competition were not revealed. In men, the bulk of the participants in the competition are on average 10 years older than in women, however, younger winners and prize-winners also appear there. The number of regions participating in competitions has decreased markedly due to the changing conditions for playing sports.